2007
DOI: 10.1007/s00432-007-0263-4
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the influence of patient race and ethnicity on expressed interest in learning about cancer clinical trials

Abstract: Assuming these provocative results regarding self-declared desire to learn about clinical trials can be confirmed by others with similar Internet-associated databases, this analysis suggests Web-based recruitment strategies may be an effective method to communicate with minority populations in the US (and, perhaps, elsewhere) with a specific interest in considering participation in cancer clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Individuals who had participated in the NexCura (Seattle, WA) oncology decision-support program 9 and previously agreed to receive information on potential future surveys were contacted by e-mail regarding their willingness to complete a questionnaire dealing with treatment-related medical expenses. Patients were specifically informed that any information they provided would be examined and reported only in the aggregate, and no individual identifiers would be provided to any researcher or other third party.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who had participated in the NexCura (Seattle, WA) oncology decision-support program 9 and previously agreed to receive information on potential future surveys were contacted by e-mail regarding their willingness to complete a questionnaire dealing with treatment-related medical expenses. Patients were specifically informed that any information they provided would be examined and reported only in the aggregate, and no individual identifiers would be provided to any researcher or other third party.…”
Section: Methodsmentioning
confidence: 99%
“…9 Reported here are the results of the responses to this survey received from this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…1) The African American percentage of the population as of the 2000 US census was 12.9%. 24 2) The Hispanic percentage of the population as of the 2000 US census was 12.5%. Table 3 Comparison population.…”
Section: Sensitivity Analysismentioning
confidence: 97%
“…23 Also, a survey of Hispanic Americans with cancer found that they are more interested in learning about clinical trials than non-Hispanic whites. 24 Despite this willingness to participate, underrepresentation of Hispanic Americans has been repeatedly documented. 9,11,25 Several hypotheses have been postulated to explain this phenomenon.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Public awareness, perceptions, and consequent attitudes toward clinical research may impact regulatory policies, guide research priorities, and shape growth in the sector; however, distrust, lack of awareness, and misconceptions of clinical research have been identified as key barriers to participation in clinical trials [61][62][63][64][65]. The PARTAKE initiative is based on the premise that an informed, participating public is invaluable for the following ethical, methodological, and operational reasons:…”
Section: Partakementioning
confidence: 99%